Fabrication of superamphiphobic surface with hierarchical structures on metal substrate - Tuo, Yanjing; Zhang, Haifeng; Chen, Liang; Chen, Weiping; Liu, Xiaowei; Song, Keguan (Colloids and surfaces. A, Physicochemical and engineering aspects, 2021)
[Display omitted] The superamphiphobic surface has attracted wide attention because of its excellent liquid-repellent property. Low sliding angle and mechanical stability are the key requirements for superamphiphobic surface to realize its potential application in industry and life. Here, the superamphiphobic surface with hierarchical micro-nano rough structures has been prepared on metal substrate by laser etching and spraying methods. The surface can repel both water and low surface tension liquids (eg. ethylene glycol, rapeseed oil, cyclohexane). The superamphiphobic surface with excellent liquid-repellent property has certain anti-fouling and drag reduction function. The prepared surface has good robustness. It shows good liquid-repellent property even if it suffers physical damage or acid/base attacks. We envision that the superamphiphobic surface will be used in a wide range of applications such as anti-fouling and liquid transportation.